Sistem Penunjang Keputusan Dalam Menentukan Jarak Terdekat Menggunakan Metode Ant Colony Optimization - Raden Wirawan Kukuh Pambudi; Surtikanti (CV. Shofanah Media Berkah, 2023)
This research was motivated by the lack of alternative options for community decision making in choosing and determining the nearest tourist attractions that can be addressed. This deficiency shows that the lack of applications that can provide solutions related to the selection of nearby tourist attractions, in general people have to manually search through the Maps application for the location of the nearest tourist attractions in their area. Therefore, the purpose of this study is to create a decision support system in determining the closest distance to tourist attractions using the Ant Colony Optimization method which aims to make it easier to determine the distance and the nearest path more effectively. So that the end result of this system can give people alternative options to get the closest route with the shortest distance more precisely. With the following results: 1. Jurang Mangu Station – Ocean Park BSD – Ricastro Waterzone – Ganespa Education Park – Trans Snow World Bintaro – Jurang Mangu Station with the shortest distance of 31.5 KM; 2. Pondok Ranji Station – Ocean Park BSD – Ricastro Waterzone – Ganespa Education Park – Trans Snow World Bintaro – Pondok Ranji Station with the shortest distance of 36 KM; 3. Rawa Buntu Station – Ricastro Waterzone – Ganespa Education Park – Trans Snow World Bintaro – Ocean Park BSD – Rawa Buntu Station with the shortest distance of 32.9 KM; 4. Serpong Station - Ricastro Waterzone - Ganespa Education Park - Trans Snow World Bintaro - Ocean Park BSD - Serpong Station with the shortest distance of 37.3 KM; 5. Sudimara Station - Ocean Park BSD - Ricastro Waterzone - Ganespa Education Park - Trans Snow World Bintaro - Sudimara Station with the shortest distance of 31.5 KM.